PENGEMBANGAN BUKU KURIKULUM MOBILE UNTUK MENINGKATKAN AKSESIBILITAS DAN EFISIENSI INFORMASI AKADEMIK PRODI TEKNOLOGI INFORMASI - nadia, nadiahusna; Marsehan, Ahmad (Universitas Majalengka, 2025)
This study focuses on the development of a mobile-based class book designed to improve the accessibility and effectiveness of academic information dissemination within the Information Technology study program. The main issues addressed include the limited availability of printed class materials, inefficiencies in updating academic information, and the absence of integrated digital solutions that support students and faculty in accessing up-to-date academic guidance. The primary objective of this research is to design and implement a mobile application that functions as a digital class book, enabling users to access academic information anytime and anywhere. This study adopts a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to thoroughly develop and evaluate the application. The Data were collected through questionnaires, interviews, and usability testing involving both students and faculty members. The results indicate that the mobile class book significantly enhances user access to academic content and improves the efficiency of information dissemination. Usability testing revealed high levels of satisfaction regarding interface design, functionality, and ease of use. Furthermore, the digital platform enables faster updates and better alignment with curriculum changes. Overall, this study demonstrates that a mobile-based solution can effectively address the limitations of traditional class material distribution methods and positively contribute to the delivery of academic services in higher education institutions.